Cytogenomic Characterization of Murine Neuroblastoma Cell Line Neuro-2a and Its Two Derivatives Neuro-2a TR-Alpha and Neuro-2a TR-Beta - Lioba Hergenhahn; Niklas Padutsch; Shaymaa Azawi; Ralf Weiskirchen; Thomas Liehr; Martina Rinčic (Cells)
Background: The Neuro-2a cell line, derived from a murine neuroblastoma (NB), was established as early as 1969 and originates from a transplantable tumor that arose spontaneously in an A/Jax male mouse in 1940. Since then, it has been applied in over 10,000 studies and is used by the World Organization for Animal Health for the routine diagnosis of rabies. Surprisingly, however, Neuro-2a has never been genetically characterized in detail; this study fills that gap. Methods: The Neuro-2a cell line and two of its derivatives, Neuro-2a TR-alpha and Neuro-2a TR-beta, were analyzed for their chromosomal constitution using molecular cytogenetic approaches. Array comparative genomic hybridization was performed to characterize copy number alterations. Results: Neuro-2A has a hyper-tetraploid karyotype with 70 to 97 chromosomes per cell, and the karyotypes of its two examined derivatives were quite similar. Neither of them had a Y-chromosome. The complex karyotype of Neuro-2a includes mitotically stable dicentres, neocentrics, and complex rearrangements resembling chromothripsis events. Although no amplification of euchromatin or oncogenes was detected, there are five derivative chromosomes with the amplification of centromere-near heterochromatic material and 1–5 additional derivatives consisting only of such material. Conclusions: Since satellite DNA amplification has recently been found in advanced human tumors, this finding may be the corresponding equivalent in mice. An in silico translation of the obtained results into the human genome indicated that Neuro-2A is suitable as a model for advanced human NB.